2018
DOI: 10.1017/gmh.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal violence and suicidality among former child soldiers and war-exposed civilian children in Nepal

Abstract: Background.Suicide risk reduction is crucial for 15–29-year-old youth, who account for 46% of suicide deaths in low- and middle-income countries. Suicide predictors in high-resource settings, specifically depression, do not adequately predict suicidality in these settings. We explored if interpersonal violence (IPV) was associated with suicidality, independent of depression, in Nepal.Methods.A longitudinal cohort of child soldiers and matched civilian children, enrolled in 2007 after the People's War in Nepal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Of the 643 potentially relevant publications screened in full text, 125 were identified as eligible for this review. The grey literature search identified another 25 eligible publications, and a further seven were identified through reference list of previous reviews, with a total of 157 publications finally included in the review 24–154Table 1. summarises the characteristics of all included publications.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 643 potentially relevant publications screened in full text, 125 were identified as eligible for this review. The grey literature search identified another 25 eligible publications, and a further seven were identified through reference list of previous reviews, with a total of 157 publications finally included in the review 24–154Table 1. summarises the characteristics of all included publications.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have looked at IPV as a particular form of interpersonal violence – covering various stages across the life course. A longitudinal study in Nepal with former child soldiers and matched civilian children ( n = 290) (on average 16 years old at the time of recruitment) found that exposure to sexual IPV (18% in women, 7% in men) was a predictor for suicidal attempts 5 years later (Bhardwaj et al ., 2018). In a longitudinal study amongst perinatal women in informal settlements in South Africa ( n = 425), IPV victimization at baseline was associated with higher levels of psychological distress, food insecurity, and rates of alcohol misuse (Schneider et al ., 2018).…”
Section: Interpersonal Violence and Mental Health: Overview Of The Sementioning
confidence: 99%
“…Suicide is the single leading cause of mortality among women of reproductive age [ 36 ], and in Jumla, the area where this study was conducted, 85% of suicides among women occur before the age of 25 years [ 37 ]. Work on suicide and mental health in this region of the country and elsewhere in Nepal has highlighted the importance of alcohol use, interpersonal conflict, thwarted life goals, emotional dysregulation, and lack of coping skills as risk factors [ 38 40 ]. The six themes were piloted in four initial interviews conducted jointly by the first and last authors and through ethnographic observation in Jumla.…”
Section: Methodsmentioning
confidence: 99%